Another modified dprp conjugate gradient method with global convergent properties - Mustafa, Mamat; Kamilu Uba, Kamfa; Mohd, Rivaie (Pushpa Publishing House, 2015)
Conjugate gradient (CG) methods play significant role in solving large scale unconstrained optimization problem, due to their low memory requirement and global convergent properties. For many years, different studies and modification have been carried out to improve this method. In this paper, we present a new CG method based on modifying the Abashar et al. [4] method (ADPRP). This new method possesses the global convergent properties and sufficient descent condition under exact line searches. Numerical result based on number of iteration and CPU time shows that the proposed coefficient is efficient and effective when compared with other CG formulas.